Technology Native, Person-Centered Integrated Care Based on Value & Choice - Ahmad, Dzulkefly (International Journal of Human and Health Sciences (IJHHS), 2019)
Malaysia – once an ‘Asian tiger’ – was an overperformer in the arena of health. Malaysia’s performance in recent years however has been less flattering. We are increasingly trailing behind comparator countries such as Taiwan, Hong Kong, Singapore, and New Zealand on the measure of life expectancy for males at age 60, a proxy measure of NCD management. The health reform agenda has been stalled for decades. Given the importance of health, at least 14 studies have been commissioned since 1985. Despite unanimous consensus on the need to reform Malaysia’s health system, critical recommendations and reforms have not yet been delivered. As needed reforms have already been postponed for several decades, the challenges faced now require a bold, phased system-wide approach described next as 3 pillars to lay the financ ia l, organizational, and regulatory foundation whose raison d'être is to establish a new healthcare model, not just incremental tweaks or partial reforms seeking to address the low hanging fruits. A Digital Shared Enabled Environment guided by international digital standards, including future-proof digitization driven by a Master Patient Index to accelerate the lifetime health record which are agile, portable across facilities, well-integrated with processes and users, can improve patient safety and provide data-driven decision as to achieve the Universal Health Coverage (UHC). A bold approach powered by a digital ecosystem would address not just the public or private sector in isolation, nor just health financing without health delivery or vice versa, but systemically improve health outcomes and reduce inequalities in an efficient manner, consistent with our national objectives which include national unity, social cohesion, and justice. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 8